A Canadian Clinical Practice Algorithm for the Management of Patients with Non-Variceal Upper Gastrointestinal Bleeding - Alan Barkun; Carlo A Fallone; Naoki Chiba; Marty Fishman; Nigel Flook; Janet Martin; Alaa Rostom; Anthony Taylor; for the Nonvariceal Upper GI Bleeding Consensus Conference Group (Canadian Journal of Gastroenterology)
AIM: To use current evidence-based recommendations to provide a user-friendly clinical algorithm for the management of upper gastrointestinal bleeding, adapted to the Canadian environment.